Global Hollywood and Home Theater. Methodological Challenges of Reception Studies. An Interview with Barbara Klinger - Skopal, Pavel (Iluminace, 2005)
An interview with American film historian Barbara Klinger and new reproduction technologies and audience relations to them, research projects in reception studies, the commercial success of the DVD format and repeat viewing, cinephilia, fans, etc.
Keywords: film historian; film scholarship and research; films on DVD; film fans; cinephilia